Correlation of undrained shear strength with in-situ testing for soft clay - Lim, Boon Lin (2014)
A series of subsurface investigation (SI) works including in-situ and laboratory tests has been carefully planned and carried out for the electrified double track embankment design. From the SI data collected, a consistent layer of 15m soft clay was found at Tokai, Kedah. The soft clay has imposes great challenges to the design work by engineer when understanding on this problematic soil is limited. This study exposes the reader to some of the physical properties and compressibility characteristic of the soft clay at Tokai, Kedah. Design of embankment over soft soil is often examined in the undrained behavior. Thus, correlations on the undrained shear strength, Su of soft clay with respect to in-situ test such as piezocone and standard penetration test are carried out in this research to enable the prediction of Su without details laboratory test. Furthermore, comparisons of the established correlations are done by comparing with the existing correlations by other researchers in order to access the suitability of those correlations on the investigated soft clay